Myoepithelial carcinoma of the parotid: a rare tumour that may provide diagnostic difficulty. (26th February 2015) - Skelton, Emily; Jewison, Amanda C; Ramesar, Keith; Howlett, David
Abstract : This report presents the case of a 57-year-old man with a 6-week history of a slowly enlarging lump in the right parotid gland. Initial ultrasound investigation confirmed a 3 cm solid mass located within the superficial lobe of the right parotid gland. Sonographically, the mass demonstrated possible malignant features with internal heterogeneity of architecture and some loss of marginal clarity. Ultrasound-guided core biopsy (USCB) of the mass reported a mixed neoplasm with epithelial and myoepithelial appearances consistent with likely benign adenoma or myoepithelioma. A right superficial parotidectomy was subsequently performed. Histological and immunohistochemical analysis of the excised specimen showed a myoepithelial carcinoma. Postoperative CT and MR staging scans did not show evidence of metastases and no further treatment was given following discussion of the case at the regional speciality multidisciplinary meeting. This case illustrates the clinical and pathological features of this rare salivary gland tumour, but also discusses the diagnostic difficulties that may be encountered preoperatively.